Socialization of Creating Learning Methods with Technology Systems for Early Childhood Education (PAUD) Children - Septiandra (Yayasan Putra Adi Dharma, 2023)
This study explores the socialization of technology-integrated learning methods for early childhood education (PAUD) children. In an era of advancing technology, it is imperative to introduce young learners to educational approaches that seamlessly integrate digital tools and systems. The research delves into the strategies employed to acquaint PAUD children with innovative learning systems. The socialization process incorporates interactive and engaging techniques designed to capture the attention and imagination of young minds. It focuses on fostering a positive attitude towards technology-assisted learning from an early age, emphasizing its potential as a valuable educational tool. Preliminary findings suggest that PAUD children, when introduced to technology-infused learning methods through carefully curated socialization programs, exhibit heightened curiosity, improved digital literacy, and enhanced engagement with educational content. This research underscores the importance of early exposure to technology-integrated learning and offers insights into effective strategies for achieving a seamless and constructive integration of technology into the educational journey of PAUD children.